Metrical Epitaphs from the Southern Suburb of Tauric Chersonesos - Almazova, Nina; Keyer, Denis; Pavlichenko, Natalia; Verlinsky, Alexander (Hyperboreus, 2024)
The paper offers the first publication of three metrical inscriptions found in the Southern Suburb of Chersonesos Taurica: a brief epitaph on the ossuary of Pharnaces, son of Dionysios (the second quarter – the middle of the 2nd cent. AD) and two marble tablets, one containing a more extended but not fully preserved epitaph of Philo, the daughter of Apollonios (2nd cent. AD), the other the fragmentary epitaph for an unknown person, possibly a warrior (the last quarter of the 2nd cent. – the 1st quarter of the 1st cent. BC).